Reduction of microbial load in poultry meat with sanitizers - Mabesa, R.C; Villaralvo, M.J.A; Melendrez, R.R (1988)
The efficacy of tap water, calcium hypochlorite (250ppm) and acetic acid (3%) in the reduction of total viable counts and fecal coliforms in chicken wings from different sources was studied. Results showed that tap water, calcium hypochlorite and acetic acid differed significantly in the reduction if total viable counts. Acetic adid give the highest percent reduction destruction. Tap water was expectedly the least effective sanitizer. Likewise acetic acid was the most effective in reducing the fecal coliforms compared to tap water and calcium hypochlorite. Lowering the concentration of acetic acid was also explored to reduce cost. it was found that all concentrations of the acid form 1 to 3% were effective in lowering total viable counts but 1% acetic acid gave a significantly lower destruction rates from sources B and C. All three concentrations of the acetic acid were effective in lowering fecal coliforms except for 1% acetic acid which exhibited a significantly lower reduction for source A. Since 2% acetic acid yielded consistently similar results to 3% samples treated at this level were subjected to sensory evaluation. At this level however, significant changes in sensory attributes of chicken wings were evident.